2024
DOI: 10.1002/adfm.202400903
|View full text |Cite
|
Sign up to set email alerts
|

Perylene Diimide‐Based Low‐Cost and Thickness‐Tolerant Electron Transport Layer Enables Polymer Solar Cells Approaching 19% Efficiency

Bin Zhang,
Yushou Zhao,
Congdi Xu
et al.

Abstract: The materials for electron transport layers (ETLs) play a significant role in the performance of polymer solar cells (PSCs) but face challenges, such as low electron transport mobility and conductivity, low solution processibility, and extreme thickness sensitivity, which will undermine the photovoltaic performance and hinder compatibility of large‐scale fabrication technique. To address these challenges, a new n‐type perylene diimide‐based molecule (PDINB) with two special amine‐anchored long‐side chains is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…PDINN-NOPN and PDI-4NOPN exhibit a deeper HOMO than PDINN, which can effectively block hole transfer from the donor to the electrode and avoid exciton recombination. This possesses a virtual effect on improving the photovoltaic performance of OSCs. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDINN-NOPN and PDI-4NOPN exhibit a deeper HOMO than PDINN, which can effectively block hole transfer from the donor to the electrode and avoid exciton recombination. This possesses a virtual effect on improving the photovoltaic performance of OSCs. , …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, inserting a quaternary ammonium salt in the PDI derivates can form extra interfacial dipoles and further adjust the performance of OSCs owing to their strong polar bromine and amine groups . Consequently, numerous PDI-based small molecules are developed and applied as high-performance CILs due to their exceptional electron transfer properties and appropriate energy levels for abstracting electrons, ,, whereas CILs with hydrophilic polar side chains are vulnerable to moisture erosion, which makes CILs obtain high surface energies (γ s ) and interfacial energies (γ ac ) and possess a poor inferior interfacial link with the active layer, ultimately affecting the PCE and stability of the device. Besides, the highly coplanar PDI core can generate unconscionable molecular aggregation, leading to a rough interface morphology and a high obstacle for electron extraction, finally hindering further elevation in the performances of OSCs. , With these concerns, in numerous studies, some bay -functionalized PDI-based CILs have been reported to tune aggregation and energy levels to meet the excellent properties of OSCs. , However, the problems of stability and PCE are rarely addressed simultaneously. Therefore, more efficient and stable PDI-based CILs need to be explored. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation